Extensive long-segment cervicothoracic traumatic spinal epidural hematoma with avulsion of C7, C8, and T1 nerve roots - Garg, Kanwaljeet (Medknow Publications & Media Pvt Ltd, 2014)
Traumatic spinal epidural hematoma (TSEH) is of rare clinical occurrence. We report a case of a young man with posttraumatic long-segment spinal epidural hematoma. Evacuation of the hematoma led to complete neurologic recovery in our patient. Our case highlights the importance of early diagnosis and prompt surgical intervention for the evacuation of hematoma in preservation or maximum recovery of neurologic function. Imaging findings, management options, and the relevant literature are reviewed.